Impacto da seleção genética na morfometria e desempenho de tilápias do nilo - Zardin, Aline Mayara da Silva Oliveira (2016)
This study aimed to estimate the variance and covariance components, genetic parameters and genetic associations of body traits and performance of Nile tilapia, Tilamax variety, grown in cages, and evaluate responses to selection and genetic evolution between generations, as well as verify the impact of selection on traits, when selecting fish based on daily weight gain. The data set used in the first study contained information of male and female tilapia grown in cages in 2011-12, 2013 and 2014. Estimates were made of variances and covariances components, genetic trends for height and tail width, trunk length, body area, harvest weight, daily weight gain and fillet volume by Bayesian Inference. An animal model considering random effects additive, residual and common family was used in additional to the fixed effects of sex and cages, in single-trait and bi-characteristics analysis. Genetic correlations between traits were positive and higher than 0.82, showing increase in traits, mainly body area and fillet volume. The heritabilities of body traits and performance were of moderate magnitude. Genetic gains were increasing to all traits, specially for daily weight gain, harvest weight, body area and fillet volume with values of 4.15, 4.59, 2.30 and 3.65% per generation, respectively. The selection based on daily weight gain resulted in indirect genetic gains in trait over the generations, changing body shape, increasing body weight with trends changing the fillet weight, as well as in the taking advantage of different cuts to the consumer market. The data set used in the second study contained information of male and female tilapia of Tilamax variety, produced in cages from 2008 to 2015. Estimates were made of variances components for total, standard and trunk length; height and width of the body, body area, harvest weight, daily weight gain and fillet volume by Bayesian inference, using single-trait analysis, in additional to genetic trends and rate of inbreeding. The heritabilities were of moderate magnitude with values between 0.14 to 0.28. The genetic trends showed increases of genetic values over the generations, with annual rates gains of 1.440 cm2 in body area, 12.90 g in harvest weight, 0.04 g day-1 in daily weight gain and 3.317 cm3 in fillet volume, representing 1.27, 2.35, 2.29 and 1.90% per generation, respectively. The rate of inbreeding showed small increment, with value of 0.36% for generation eight. The heritabilities values and genetic variances over the generations showed the genetic progress and response to selection, with the main gains in traits body area, harvest weight, daily weight gain and fillet volumes without reducing the genetic variability and with small increment of inbreeding, which enables genetic gains on future generations.